Normative Data for Median Nerve Conduction in Healthy Young Adults from Punjab, India - Singh, Manjinder (J Neurosci Rural Pract, 2017)
BACKGROUND: Nerve conduction studies (NCSs) are essential for diagnosing various kinds of focal and diffuse neuropathies. Due to the paucity of local NCS data, electrodiagnostic laboratories in Punjab rely on values from Western and other Indian studies. AIM: This study was conducted to provide normative data for median nerve conduction parameters (motor and sensory) in Punjabi populace. MATERIALS AND METHODS: A cross-sectional study was done on 290 participants (150 males and 140 females), aged 17–21 years, as per standardized protocol. The data were analyzed separately for both genders using SPSS version 20. It consisted of distal latencies and conduction velocities of motor and sensory divisions of median nerve. Student's unpaired t-test was used for statistical analysis. RESULTS: There was no effect of gender on any of the median nerve conduction parameters. Height and weight had nonsignificant negative and positive correlation, respectively (P > 0.05), with conduction velocity in both motor and sensory median nerves. For median motor nerve, the values of distal latency and conduction velocity in males were 2.9 ± 0.16 ms and 60.25 ± 2.99 m/s, respectively, whereas, in females, they were 2.6 ± 0.43 ms and 59.83 ± 2.82 m/s. Similarly, for median sensory nerve, the latency and velocity values in males were 2.8 ± 0.56 ms and 54.81 ± 3.70 m/s, whereas, in females, they were 2.4 ± 0.33 ms and 54.56 ± 3.65 m/s, respectively. CONCLUSION: The data in this study compared favorably with already existing data. It would help the local electrodiagnostic laboratories in assessing the median nerve abnormalities with greater accuracy in this population subset.